Quantitative ER ↔ Golgi Transport Kinetics and Protein Separation upon Golgi Exit Revealed by Vesicular Integral Membrane Protein 36 Dynamics in Live Cells - Dahm, Thorsten (The American Society for Cell Biology, 2001)
To quantitatively investigate the trafficking of the transmembrane lectin VIP36 and its relation to cargo-containing transport carriers (TCs), we analyzed a C-terminal fluorescent-protein (FP) fusion, VIP36-SP-FP. When expressed at moderate levels, VIP36-SP-FP localized to the endoplasmic reticulum, Golgi apparatus, and intermediate transport structures, and colocalized with epitope-tagged VIP36. Temperature shift and pharmacological experiments indicated VIP36-SP-FP recycled in the early secretory pathway, exhibiting trafficking representative of a class of transmembrane cargo receptors, including the closely related lectin ERGIC53. VIP36-SP-FP trafficking structures comprised tubules and globular elements, which translocated in a saltatory manner. Simultaneous visualization of anterograde secretory cargo and VIP36-SP-FP indicated that the globular structures were pre-Golgi carriers, and that VIP36-SP-FP segregated from cargo within the Golgi and was not included in post-Golgi TCs. Organelle-specific bleach experiments directly measured the exchange of VIP36-SP-FP between the Golgi and endoplasmic reticulum (ER). Fitting a two-compartment model to the recovery data predicted first order rate constants of 1.22 ± 0.44%/min for ER → Golgi, and 7.68 ± 1.94%/min for Golgi → ER transport, revealing a half-time of 113 ± 70 min for leaving the ER and 1.67 ± 0.45 min for leaving the Golgi, and accounting for the measured steady-state distribution of VIP36-SP-FP (13% Golgi/87% ER). Perturbing transport with AlF(4)(−) treatment altered VIP36-SP-GFP distribution and changed the rate constants. The parameters of the model suggest that relatively small differences in the first order rate constants, perhaps manifested in subtle differences in the tendency to enter distinct TCs, result in large differences in the steady-state localization of secretory components.